2018
DOI: 10.1080/08998280.2018.1499293
|View full text |Cite
|
Sign up to set email alerts
|

Impact of angiotensin-converting enzyme inhibitors and statins on viral pneumonia

Abstract: Angiotensin-converting enzyme (ACE) inhibitors and statins may potentially benefit patients with viral infections and pneumonia. Our study aimed to evaluate the impact of ACE inhibitors and statins on the rates of intubation and death in viral pneumonia. We retrospectively studied 1055 adult patients admitted to a tertiary care center in central Texas with a positive respiratory viral polymerase chain reaction test. Of these, 539 had clinical presentation and imaging consistent with pneumonia. We collected inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 32 publications
5
101
0
8
Order By: Relevance
“…In addition, lower proportion of patients with COVID-19 overall were on ARBs or ACEIs than expected 27,28 raising the possibility that concerns regarding these drugs at the beginning of the epidemic may have resulted in change in medication in patients on admission, In-hospital use of ACEI has previously been shown to be associated with lower rate of ventilation and inhospital mortality with viral pneumonias. 29 Our case-control analysis showed that those taking CCBs had significantly increased risk [OR 1.67 (95% CI 1.2-2.9)] of manifesting symptoms of COVID-19. In addition, patients on beta-blockers were more likely to develop severe (13.2%) and critical form (21.1%) compared to mild/ common form (6.6%) of the disease but this last analysis was not significant after adjusting for age sex and BMI.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 68%
“…In addition, lower proportion of patients with COVID-19 overall were on ARBs or ACEIs than expected 27,28 raising the possibility that concerns regarding these drugs at the beginning of the epidemic may have resulted in change in medication in patients on admission, In-hospital use of ACEI has previously been shown to be associated with lower rate of ventilation and inhospital mortality with viral pneumonias. 29 Our case-control analysis showed that those taking CCBs had significantly increased risk [OR 1.67 (95% CI 1.2-2.9)] of manifesting symptoms of COVID-19. In addition, patients on beta-blockers were more likely to develop severe (13.2%) and critical form (21.1%) compared to mild/ common form (6.6%) of the disease but this last analysis was not significant after adjusting for age sex and BMI.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 68%
“…Mice with coronavirus induced lung injury showed improvement when treated with losartan [39]. Moreover, a retrospective analysis found reduced rates of death and endotracheal intubation in patients with viral pneumonia who were continued on ACE inhibitors [40]. Treatment with ARBs was reported to reduce mortality in Ebola virus infection [41].…”
Section: Effects Of Ace Inhibitors and Angiotensin Receptor Blockersmentioning
confidence: 99%
“…A secondary analysis of a 2010 randomized control trial in patients with acute respiratory failure suggested that treatment with ACEi/ARB at discharge following an episode of acute respiratory failure was associated with a 44% reduction in 1-year mortality [81]. More recently, Hsieh et al85] and continuation of RAAS inhibitor therapy during admission is associated with decreased hospital mortality and odds of intubation in viral cases of pneumonia [86]. RAAS may have implications for other viral pneumonias, as well, as Gu et al found that children with respiratory syncytial virus tend to have higher Ang II levels compared to healthy children [87].…”
mentioning
confidence: 99%